A comparative study between I-gel and endotracheal tube in elective laparoscopic cholecystectomy surgeries under general anesthesia - Kapil Ahirwar; Suman Gupta; Abhishek Gupta; Suman Prabha Tirkey; Preeti Goyal (Asian Journal of Medical Sciences, 2023)
Background: With increase in incidence of gall bladder stone the laparoscopic cholecystectomy preferred in various hospitals. Laryngoscopic stimulation of oropharyngeal and laryngeal structures leads to hemodynamic stress response. I-gel is a second generation supraglottic airway device with noninflatable cuff, having several advantages such as minimal hemodynamic changes during insertion and easy to insert. Aims and Objectives: The aim of this study was to compare I-gel and endotracheal tube regarding hemodynamic stability, adequacy of ventilation, ease of insertion through number of attempts, and time for insertion and associated complications in patients undergoing laparoscopic cholecystectomy. Materials and Methods: Total 60 patients of either sex, 25–55 years age of ASA Grades I and II were randomly allocated into two groups of 30 patients each; Group A (endotracheal tube) and Group B (I-gel). Ease of insertion in terms of number of attempts and time for insertion, hemodynamic variation and their complications were recorded. Results: Significantly less time was required for insertion of I-gel as compared to endotracheal tube (P=0.04), while number of attempts required for insertion were comparable, highly significant difference in heart rate, systolic blood pressure, mean arterial pressure just after insertion and at extubation of endotracheal tube than I-gel group (P<0.01), peak airway pressure at insufflation with endotracheal tube was highly significant (P<0.01), and SPO2 and ETCO2 were comparable. The complications were statistically insignificant among the study groups. Conclusion: Comparison to endotracheal tube, I-gel required less time and less number of attempts for insertion and causes fewer hemodynamic alterations. In addition, peak airway pressure was also significantly more in endotracheal tube just before and at pneumoperitoneum.